Inversion Calculation Analysis of Operational Tunnel Structure Based on the Distributed Optical-Fiber Sensing System - Jie Zhao; Jiang Feng; Liang Ren (Advances in Civil Engineering)
In combination of the actual project in Dalian Baiyun Mountain Tunnel, this paper introduces the principle of fiber optic sensor monitoring system based on optical time domain reflectometer. Then, based on the orthogonal design and even design scheme, this paper carries out a numerical experiment on the tunnel surrounding rock and establishes a regression model of the mapping relation between surrounding rock parameters of operation tunnel and the monitored displacement in order to set the difference between the monitored displacement and the calculated displacement as the fitness function. In the end, this paper carries out parameter identification based on the differential evolution algorithm. Achievements of the study proved that real-time safety warning could be realized inside the tunnel by monitoring the deformation parameters of tunnel vault at real time relying on the optical-fiber sensing system of the optical time domain reflectometer (OTDR). Parameters identification was carried out on the structure with differential evolution according to measured data and selected parameters, and great coincidence was obtained between the measured displacement and the identified parameters displacement, which proved the strong adaptability of the method.